A Multifunction Infant Incubator Monitoring System with Phototherapy and ESP-32 Based Mechanical Swing - Fadilla, Rafa; Andi Nurul Isri Indriany Idhil; Monika Ayu Puji Anggraini; Ajeng Kusuma Dewi; Mochammad Rofi Sanjaya; Muhammad Yogi Nurrohman; Rahmadwati (Publisher Cv. Inara, 2020)
Many infant mortality rates are due to premature events. Premature babies are at high risk for hypothermia and hyperbilirubinemia. To overcome this, an incubator can be used as a warmer and light therapy as blue light therapy for yellow babies. However, both medical devices have still been found using manual control. If the health worker is tired of working and manually controlling both devices, it can put the baby at risk. Multifunctional infant incubator based on ESP32, which is an infant incubator equipped with phototherapy and a mechanical swing. This multifunctional baby incubator has the ability to warm the baby's body, the baby yellow light therapy, and can calm the baby when crying. This tool can be monitored remotely using the Internet of Things (IoT). The sensors used are the DHT22 sensor and the sound sensor. Multifunctional baby incubator can make it easier for hospital or basic health care facility level to monitor baby's health in real time without being at the device location and the resulting data can be stored neatly.